Facioscapulohumeral muscular dystrophy and respiratory failure; what about the diaphragm? - A. Hazenberg; N. van Alfen; N.B.M. Voet; H.A.M. Kerstjens; P.J. Wijkstra (Respiratory Medicine Case Reports, 2015)
Introduction: We present a case of facioscapulohumeral muscular dystrophy (FSHD) with a diaphragm paralysis as the primary cause of ventilatory failure. FSHD is an autosomal dominant inherited disorder with a restricted pattern of weakness. Although respiratory weakness is a relatively unknown in FSHD, it is not uncommon. Methods: We report on the clinical findings of a 68-year old male who presented with severe dyspnea while supine. Results: Supplementing our clinical findings with laboratory, electrophysiological and radiological performances led to the diagnosis of diaphragm paralysis. Arterial blood gas in sitting position without supplemental oxygen showed a mild hypercapnia. His sleep improved after starting non-invasive ventilation and his daytime sleepiness disappeared. Discussion: We conclude that in patients with FSHD who have symptoms of nocturnal hypoventilation, an adequate assessment of the diaphragm is recommended. This is of great importance as we know that nocturnal hypoventilation can be treated effectively by non-invasive ventilation.